Study of MG49-PMMA based solid polymer electrolyte - Ahmad A.; Rahman M.Y.A.; Su'ait M.S.; Hamzah H. (2023)
The studies of rubber-polymer blends as solid polymer electrolyte for electrochemical devices application have been investigated. The electrolyte films were prepared by solution casting technique. The effect of poly(methyl methacrylate) (PMMA) and lithium tetrafluoroborate (LiBF4), salt concentration on chemical interaction, ionic conductivity, structure and morphology of 49% poly(methyl methacrylate)-grafted natural rubber (MG49) have been analyzed by using fourier transform infrared spectroscopy (FT-IR), electrochemical impedance spectroscopy (EIS), x-ray diffraction (XRD) and scanning electron microscopy (SEM). Infrared analysis showed that the interaction between oxygen atoms and lithium ion occurred at ether (C-O-C) and carbonyl (C=O) group in the MMA host. The highest ionic conductivity for blended MG49-PMMA films is 8.310-6 S cm-1 as compared to MG49 electrolyte with 9.610-10 S cm-1 at 25 wt. % LiBF4. The structural analysis showed the reduction of MMA crystallinity phase at the highest conductivity for both systems. Meanwhile, morphological analysis shows that recrystallization of LiBF4 salts have occurred in the electrolyte system after the optimum conductivity. Ahmad et al.